Supplementing Closed Ecological Life Support Systems with In-Situ Resources on the Moon - Alex Ellery (Life, 2021)
In this review, I explore a broad-based view of technologies for supporting human activities on the Moon and, where appropriate, Mars. Primarily, I assess the state of life support systems technology beginning with physicochemical processes, waste processing, bioregenerative methods, food production systems and the robotics and advanced biological technologies that support the latter. We observe that the Moon possesses in-situ resources but that these resources are of limited value in closed ecological life support systems (CELSS)—indeed, CELSS technology is most mature in recycling water and oxygen, the two resources that are abundant on the Moon. This places a premium on developing CELSS that recycle other elements that are rarified on the Moon including C and N in particular but also other elements such as P, S and K which might be challenging to extract from local resources. Although we focus on closed loop ecological life support systems, we also consider related technologies that involve the application of biological organisms to bioregenerative medical technologies and bioregenerative approaches to industrial activity on the Moon as potential future developments.